Fatores de risco sócio-ambientais para o binômio teníase-cisticercose em um bairro da periferia de Goiânia, Goiás-Brasil - SILVA, Delson José da (2006)
The taeniasis-cysticercosis complex imposes a serious problem to the public health system especially in developing and poor countries In a cross-sectional exploratory descriptive study it was attempted to investigate environmental and epidemiologic factors associated with disease transmission in an outskirts` poor district of the city of Goiânia - Brazil where potential risk factors for this disease have been detected The sample was made up of 12.895 subjects (75% of the local population) who voluntarily answered a questionnaire containing information concerning demographics hygienic and alimentary habits swine raising technique place of human stool disposal and seizure history The investigating team was composed of volunteers and health sciences professionals and students Statistical analysis showed the following statistically significant results: 588 of the subjects with seizure history 11,2% presented cysticercosis; taeniasis was more prevalent in female subjects with age ranging from 40 to 49 years (7%; p=0.00); the diagnosis of taeniasis was established in 4.02% (p=0.00) of the subjects who consumed pork (80.41%) in 100% (p=0.00) of those who consumed raw meat in 5.93% (p=0.00) of the subjects who consumed meat more than once a week in 7.44% (p=0.00) of those who drank water from the well in 6.7% (p=0.03) of the subjects who currently raise swine in 15.6% (p=0.00) of those who raise swine in the surroundings of their home and in 25% (p=0.00) of the subjects with outdoor defecation habit Our findings strongly suggest that the detection of the various factors involved in the acquisition and maintenance of the taeniasis-cysticercosis complex are of utmost importance for the adoption of appropriate measures aiming to interrupt the life cycle of this parasitosis which is a consequence of the relationships between humans environment and swine